Pengaruh Gaya Kepemimpinan dan Self Efficacy terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Kantor Sekretariat Daerah Kabupaten Gunungkidul) - Ramadhani Wahyuningtyas; Kusuma Chandra Kirana (Universitas Batanghari Jambi, 2022)
The existence of knowledge about the analysis of the influence of Leadership Style and Self Efficacy at Job Satisfaction and Employee Performance in the Regional Secretariat Office of Gunungkidul Regency. Probability sampling method and using simple random sampling with the employees of the Regional Secretariat Office of Gunungkidul Regency with respondents 56 employees. The implementation of research using an instrument in the form of a questionnaire using SPSS 24 to analyze it. Researchers took the results leadership style significantly had no influence on employee performance, leadership style significantly had no influence on job satisfaction, self-efficacy significantly had an influence on employee performance, self-efficacy significantly had an influence on job satisfaction, and job satisfaction significantly has no influence on employee performance.